What the Army needs to know to align its operational and institutional activities - Camm, Frank A., 1949- (RAND, 2007)
The Army must transform its institutional activities to align them with operating forces to improve support and release resources from institutional activities. This document provides a model for evaluating value chains to promote the alignment of needs and resources according to three representational institutional Army activities: medical services, enlisted accessioning, and short-term acquisition.